Search for pair-produced resonances decaying to quark pairs in proton-proton collisions at √s=13 TeV - Sirunyan A. M.; Tumasyan A. R.; Adam W. Wolfgang; Ambrogi F. Federico; Babaev A. A. Anton Anatoljevich; Okhotnikov V. V. Vitaly Vladimirovich (2018, 2018)
Title screen